Tingkat Perkembangan Motorik Kasar Pada Anak Pra Sekolah di Perumahan Symphony Banguntapan Bantul Yogyakarta - FERI YULIANI; Putri Kusumawati Priyono; Aminatul Fatayati; Rizal Fajri; Rina Asih Budi Cahyaningrum; syolichah (Universitas Muhammadiyah Klaten, 2026)
The preschool period (3-5 years old) is a critical period in children's physical development, especially gross motor skills, which involve controlling large muscles for activities such as walking, running and jumping. Optimal development in this phase is very important as a foundation for future physical skills. The living environment, including play facilities and social interaction in housing, is thought to influence children's motor stimulation. This research aims to identify and describe the level of gross motor development of preschool-age children in the specific environment of the Symphony Banguntapan Housing Complex, Bantul, Yogyakarta. This research uses a quantitative approach with descriptive methods. The research population included all children aged 3-5 years who lived in the Symphony Banguntapan Housing Complex, Bantul, Yogyakarta. The sampling technique was carried out by total sampling or purposive sampling. Data was collected through direct observation using an instrument in the form of a standard gross motor development checklist (DDST II/Denver Developmental Screening Test II). Data analysis was carried out using descriptive statistics to present data in the form of frequency distributions and percentages to determine categories of development level. The research results showed that the majority of preschool children at Symphony Banguntapan Housing had a level of gross motor development in the